2014
DOI: 10.5056/jnm14026
|View full text |Cite
|
Sign up to set email alerts
|

Bone Marrow Derived Kit-positive Cells Colonize the Gut but Fail to Restore Pacemaker Function in Intestines Lacking Interstitial Cells of Cajal

Abstract: Background/AimsSeveral motility disorders are associated with disruption of interstitial cells of Cajal (ICC), which provide important functions, such as pacemaker activity, mediation of neural inputs and responses to stretch in the gastrointestinal (GI) tract. Restoration of ICC networks may be therapeutic for GI motor disorders. Recent reports have suggested that Kit + cells can be restored to the GI tract via bone marrow (BM) transplantation. We tested whether BM derived cells can lead to generation of func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Similar findings were also reported along with improved gastric emptying in W/W v mutant mice [ 108 ]. However, McCann et al [ 109 ] found that when GFP + Kit + bone-marrow-derived cells (from Kit +/copGFP mice) were transplanted into the small intestine of W/W v mutant mice, they did not observe these cells differentiate into network-forming ICC-like cells. These contradictory findings indicate more detailed molecular and functional characterisation of the transplanted cells is needed before the potential utility of this approach can be properly assessed.…”
Section: Icc and Gi Therapymentioning
confidence: 99%
“…Similar findings were also reported along with improved gastric emptying in W/W v mutant mice [ 108 ]. However, McCann et al [ 109 ] found that when GFP + Kit + bone-marrow-derived cells (from Kit +/copGFP mice) were transplanted into the small intestine of W/W v mutant mice, they did not observe these cells differentiate into network-forming ICC-like cells. These contradictory findings indicate more detailed molecular and functional characterisation of the transplanted cells is needed before the potential utility of this approach can be properly assessed.…”
Section: Icc and Gi Therapymentioning
confidence: 99%
“…However, it is not clear whether increased unitary potential but no slow wave observed in this study 23 is sufficient to accelerate intestinal transit observed in Ishii's study, 22 since electrophysiological study was not performed in Ishii's study. 22 Further study is required.…”
mentioning
confidence: 64%
“…Western blot analysis was performed using standard techniques and as previously described ( 27 ). Details are provided in the Supplementary Data .…”
Section: Methodsmentioning
confidence: 99%